Texto tecido no corpo da palavra: das linhas de Guimarães Rosa às costuras de Ronaldo Fraga - Fogolari, Luan Henrique (2019)
This study aims at describing the interconnection between fashion and literature. The objective is to understand the syncretic relationship between the literary work Grande Sertão: Veredas, by Guimarães Rossa and the fashion show A cobra ri, by fashion designer Ronaldo Fraga. For that, it reflects on the importance of the body and the garments for the construction of the fashion system, identifying regimes, connections and the modeling of cultural identity constructions in which it is inserted. Based on theories by Massimo Canevacci (2005, 2008, 2013), this research attempts to comprehend how these two autonomous languages are interwoven; also, where the clothing assumes the role of the text, and how its fabrics converge and reconfigure other conversational territories. Such study proposes the analysis of some photographs of the fashion show A cobra ri, based on the premise that Fraga’s work charts a narrative which establishes itself through a syncretism of codes and sources, relating fashion and literature, specifically Rosa’s work, Grande Sertão: veredas. This qualitative and bibliographical investigation offers a close look at the syncretic and semiotic interrelations of the elements from the Rosean production and universe incorporated in the garments created by Fraga, pondering different forms and experimentations, be it in the languages or between the codes in polyphony and intersemiosis.